Physicochemical, Physical Characteristics and Antioxidant Activities ofThree Edible Red Seaweeds (Kappaphycus alvarezii, Eucheumaspinosum and Eucheuma striatum) from Sabah, Malaysia - Farah Nurshahida, M. S.; Nazikussabah, Zaharudin; Subramaniam, S.; Wan Faizal, Wan Ishak; Nurul Aini, Mohd Azman (IOP Publishing, 2020)
Kappaphycus alvarezii(KA), Eucheuma spinosum(ESp) and Eucheuma striatum(Estare tropical red seaweeds taken from Kunak, Sabah, contain essentialssource of bioactive compounds to producevariety of functional foods. This study was intendedto investigate the physicochemical, physicalproperties and antioxidant activities related to these edible seaweeds.Physicochemical properties value of swelling capacity (SWC) and oil retention capacity (ORC) in KA species showed the highestvalue(p<0.05) comparedto ESp and ESt,and water retention capacity (WRC)in ESp species was significantly different than KA and ESt (p<0.05).As in physical properties, ESp exhibitedhigher in moisture content and opacity than KA and ESt. KA showed the highest water solubility (p<0.05)which associated to itscarrageenan compound.The antioxidant activities; DPPH and TEAC assaywithtotal phenolic content (TPC) of three seaweedspecies indicated that KA displayed the highest TPC (19.17±0.04 mg GAE/g DW) and the lowest radical scavenging activity in both TEAC and DPPH assays. Hence, thefindings disclose the physical and physiochemical properties and antioxidant values of these seaweeds applicationas newinformation and potential antioxidant sources in foods manufacturing commodities.